Problems of regulating the quality of medical care in Ukraine and the main directions of their solution - K.O. Tolstanov; A.G. Krut; I.A. Dmitrenko; V.V. Gorachuk (Medičnì Perspektivi)
Improving the quality of health care remains problem of the day for world health systems.  Recognized quality management tools are used in Ukraine. However, a series of studies indicate the need for their improvement.. The aim of this work was to determine the features of the application of international instruments for regulating the quality of medical care and to substantiate the conceptual directions of their improvement in Ukraine. Materials and methods of research used: systemic approach; comparative analysis; bibliosemantic; conceptual modeling; scientific literature sources, including systematic reviews from the PubMed database; domestic legal documents. Main results: unlike international practices, professional activity of doctors is not licensed in Ukraine. The economic activity of health care institutions and individuals-entrepreneurs engaged in medical practice is subject to licensing. Аccreditation standards have not been revised since 2013. Domestic adaptation of clinical guidelines has been suspended for several years. Certification of quality management systems is administratively related to accreditation. All quality management tools are strictly regulated by the Ministry of Health, without the involvement of local governments, public patient organizations and health professionals. Conceptual directions of improvement of tools of quality regulation are offered: adoption of the law on professional licensing of doctors; creation of an independent accreditation agency; updating the content of accreditation standards, supplementing them with patient safety standards in accordance with international criteria; creation of methodological support for accreditation and certification; training of accreditation inspectors; introduction of tracer methodology in order to verify compliance with accreditation standards; resumption of adaptation of international clinical guidelines at the health sector.